Generation of an Oncolytic Herpes Simplex Viral Vector Completely Retargeted to the GDNF Receptor GFRα1 for Specific Infection of Breast Cancer Cells - Bonnie L. Hall (International Journal of Molecular Sciences, 2020)
Oncolytic herpes simplex viruses (oHSV) are under development for the treatment of a variety of human cancers, including breast cancer, a leading cause of cancer mortality among women worldwide. Here we report the design of a fully retargeted oHSV for preferential infection of breast cancer cells through virus recognition of GFRα1, the cellular receptor for glial cell-derived neurotrophic factor (GDNF). GFRα1 displays a limited expression profile in normal adult tissue, but is upregulated in a subset of breast cancers. We generated a recombinant HSV expressing a completely retargeted glycoprotein D (gD), the viral attachment/entry protein, that incorporates pre-pro-GDNF in place of the signal peptide and HVEM binding domain of gD and contains a deletion of amino acid 38 to eliminate nectin-1 binding. We show that GFRα1 is necessary and sufficient for infection by the purified recombinant virus. Moreover, this virus enters and spreads in GFRα1-positive breast cancer cells in vitro and caused tumor regression upon intratumoral injection in vivo. Given the heterogeneity observed between and within individual breast cancers at the molecular level, these results expand our ability to deliver oHSV to specific tumors and suggest opportunities to enhance drug or viral treatments aimed at other receptors.